2-octynoic acid inhibits hepatitis C virus infection through activation of AMP-activated protein kinase. - Darong Yang; Binbin Xue; Xiaohong Wang; Xiaoyan Yu; Nianli Liu; Yimin Gao; Chen Liu; Haizhen Zhu (PLoS ONE, 2013)
Many chronic hepatitis C virus (HCV)-infected patients with current therapy do not clear the virus. It is necessary to find novel treatments. The effect of 2-octynoic acid (2-OA) on HCV infection in human hepatocytes was examined. The mechanism of 2-OA antiviral activity was explored. Our data showed that 2-OA abrogated lipid accumulation in HCV replicon cells and virus-infected hepatocytes. It suppressed HCV RNA replication and infectious virus production with no cytotoxicity to the host cells. 2-OA did not affect hepatitis B virus replication in HepG2.2.15 cells derived from HepG2 cells transfected with full genome of HBV. Further study demonstrated that 2-OA activated AMP-activated protein kinase (AMPK) and inhibited acetyl-CoA carboxylase in viral-infected cells. Compound C, a specific inhibitor of AMPK, inhibited AMPK activity and reversed the reduction of intracellular lipid accumulation and the antiviral effect of 2-OA. Knockdown of AMPK expression by RNA interference abolished the activation of AMPK by 2-OA and blocked 2-OA antiviral activity. Interestingly, 2-OA induced interferon-stimulated genes (ISGs) and inhibited microRNA-122 (miR-122) expression in virus-infected hepatocytes. MiR-122 overexpression reversed the antiviral effect of 2-OA. Furthermore, knockdown of AMPK expression reversed both the induction of ISGs and suppression of miR-122 by 2-OA, implying that activated AMPK induces the intracellular innate response through the induction of ISGs and inhibiting miR-122 expression. 2-OA inhibits HCV infection through regulation of innate immune response by activated AMPK. These findings reveal a novel mechanism by which active AMPK inhibits HCV infection. 2-OA and its derivatives hold promise for novel drug development for chronic hepatitis C.